PENGARUH KEBIJAKAN LIBERALISASI PERDAGANGAN TERHADAP PERUBAHAN EKSPOR DAN IMPOR DI INDONESIA - Jamal Nasir Baso (JEP (Jurnal Ekonomi Pembangunan), 2017)
This study aims to determine the effect of trade liberalization policies on changes in exports and imports in Indonesia during the period 1996-2007. The type of data used is secondary data. The analysis tool uses Simple Linear Regression. Based on the results of the discussion between export and export taxes, R results are 0.787 while the contribution is R2 = 0.619 or 61.9 percent. Based on the t-test partially the export tax (X) has a significant effect on exports (Y) (t = 4.031> t table 1,812) and significance = 0.002 < α = 0.05 so reject H0 accept H1. While the results of the analysis between import duties and imports are obtained in the form of R amounting to 0.812 while the contribution of import duty and import is R2 = 0.673 or 67.3 percent. Based on the t-test partially the import duty (X) has a significant effect on the import variable (Y) (t stat = 4,541> t table = 1,812) and significance = 0.001 < α = 0.05, then reject H0 accept H1. Based on the results of the analysis it can be concluded that the export tax has a significant effect on exports and also the import duty has a significant effect on imports. So that in this case the policy of trade liberalization through export taxes and import duties significantly affected the development of exports and imports.